Comparative analysis of income trends and perceived value of squad of the highest turnover European football clubs (2010-2019) - Benito Pérez-González; Luis de la Riva; José Bonal; Alvaro Fernández-Luna (European Journal of Government and Economics (EJGE), 2020)
The purpose was to analyse the income variation of the 13 top clubs of Deloitte Football Money League Report (2019) as well as the variation of the perceived value of their squad, obtained from the website www.transfermarkt.es during 9 seasons. Friedman's two-way analysis by ranges of selected samples and Wilcoxon W tests were used to measure the evolution and relation among the clubs' income and perceived value of players. The income of clubs was deflected according to inflation (CPI: 2016) and market value was adjusted to a 20 players squad. Market value and income have a significant positive variation from one year to the next (p = .000). We found differences between both variables only in the last 2 years on the period analysed (2011-2019). Market value has suffered an increase higher than expected. This fact should make football managers reflect on how to control constant inflation in the transfer market.
Keywords: L51; L83; M10; Z20; 330; Financial Fair Play; football; revenue; perceived value; transfer market